E-cigarette use, psychological distress, and daily activity participation among adults in Riyadh - Aljohani, Fenoon Abdullah; Alzubaidi, Bakriah Yahyaa; Al-Rafdan, Reem Hamdan; Alblawi, Hanan Mutiq; Alrehayan, Rama Hani; Alsenan, Ghada Abdulrahman; Almohaya, Hadeil Salman; Taha, Mona Mohamed (Frontiers in Psychiatry, 2024)
The prevalence of e-cigarettes is significantly increasing among adults as an alternative method to tobacco smoking. However, the chemical products of e-cigarettes have an influence on human general health. Therefore, this study aims to investigate the association between ecigarette use and psychological distress as well as participation in daily activities among adults in Riyadh, Saudi Arabia. It also evaluates the demographic profile and usage patterns of ecigarette users.This cross-sectional study involved 396 e-cigarette smokers in Riyadh city. An online survey was administered, including questions about smoking patterns and the perceived effects of ecigarettes on activities of daily living. Additionally, mental health were assessed using the Kessler 6 scale.Most of the participants were educated young males (61.4%). About 29.5% of the participants reported using e-cigarettes primarily to quit tobacco cigarettes. In addition, e-cigarette usage was significantly associated with lower participation in activities of daily living and higher psychological distress.This study found that many e-cigarette users are well-educated young individuals who use ecigarettes as a substitute for traditional cigarettes. However, the study also revealed that using e-cigarettes is associated with negative effects on smokers' daily activities and mental health.